Western and Non-Western Meaning of the left-right divide across four continents - Freire, A.; Kivistik, K. (Journal of Political Ideologies, 2013)
By using data from the Comparative National Election Project, we first map how widespread the Western meanings of the left-right (LR) divide are across four continents. Second, using hierarchical regressions, we explain variation in the value anchoring (Western meanings) of LR both across individuals and countries. Finally, we explore the relationships between LR and major 'Western' and 'non- Western' value conflicts. Results confirm that the 'Western' template of values has a significant impact on the LR divide across the globe, and also that their importance is higher in Europe and the US than in other regions. Additionally, we find that 'non- Western' values (namely topics related to state paternalism, attitudes towards the normality of conflict, cultural nationalism and multiculturalism) do structure the LR divide, above all in non-Western regions. Hence, the inclusion of items designed to tap these non-Western issues is more than justified for future research.